1976
DOI: 10.1111/j.1365-2362.1976.tb00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Adaptation of Bicarbonate Excretion Following Acute Contralateral Kidney Exclusion in the Dog

Abstract: Changes in the excretion of bicarbonate, sodium and potassium in one kidney after exclusion (complete sudden ligation of renal pedicle) of its partner have been studied in 16 dogs undergoing bicarbonate diuresis. Fluid balance, haematocrit, plasma electrolyte and protein concentrations were maintained constant throughout the experiment. Acute contralateral renal pedicle ligation lead to an immediate increase in bicarbonate as well as water, sodium and potassium excretion by the remaining kidney. The rapid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
5
4
0
Order By: Relevance
“…For these reasons, it seems logical to interpret the increased cation excretion after uninephrectomy in the present studies as resulting from decreased proximal reabsorption, and increased distal delivery, of filtered sodium bicarbonate, leading to increased distal potassium secretion. Increased cation excretion, chiefly potassium, then results, accompanied presumably by bicarbonate (13). The constancy of Uc1V in these experiments is consistent with this formulation.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…For these reasons, it seems logical to interpret the increased cation excretion after uninephrectomy in the present studies as resulting from decreased proximal reabsorption, and increased distal delivery, of filtered sodium bicarbonate, leading to increased distal potassium secretion. Increased cation excretion, chiefly potassium, then results, accompanied presumably by bicarbonate (13). The constancy of Uc1V in these experiments is consistent with this formulation.…”
Section: Resultssupporting
confidence: 76%
“…The delivery of significant quantities of relatively nonreabsorbable anions such as bicarbonate and sulfate accelerate potassium secretion and lead to increased UKV. In this regard, earlier studies have shown that contralateral kidney clamping causes an increase in urinary sodium bicarbonate excretion (13,15). For these reasons, it seems logical to interpret the increased cation excretion after uninephrectomy in the present studies as resulting from decreased proximal reabsorption, and increased distal delivery, of filtered sodium bicarbonate, leading to increased distal potassium secretion.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…A vasopressin-mediated increase in cation excretion does not seem likely in the present studies, since similar increments were seen after AUN in intact animals and in dogs given atropine; vasopressin levels should not be affected by the administration of atropine (Schrier and Berl, 1972). In addition, the natriuretic response to AUN has been demonstrated in dogs receiving a constant infusion of ADH (Guignard and Dirks, 1976b). A possible role of other humoral factors in mediating the response has been suggested (Coe et al, 1968;Dirks and Wong, 1978).…”
Section: Discussionsupporting
confidence: 67%
“…The small increment in electrolyte excretion in the face of a large decrease in proximal reabsorption has been attributed to reabsorption in distal nephron segments of much of the increment in fluid delivered out of the proximal tubule. The predominance of increased UKV also has been interpreted as reflecting enhanced distal tubular Na + :K + exchange resulting from increased distal Na + delivery (Guignard and Dirks, 1976b;Humphreys and Ayus, 1978). The identification of a primarily proximal locus of action is remarkable in view of the renal hemodynamic findings shown in Table 2: AUN in group B dogs was accompanied by increases in filtration fraction and renal vascular resistance, changes generally associated with enhanced proximal reabsorption and decreased electrolyte excretion.…”
Section: Discussionmentioning
confidence: 99%